2022
DOI: 10.1002/oby.23519
|View full text |Cite
|
Sign up to set email alerts
|

Xenon‐enhanced computed tomography assessment of brown adipose tissue distribution and perfusion in lean, obese, and diabetic primates

Abstract: Objective This study aimed to validate xenon‐enhanced computed tomography (XECT) for the detection of brown adipose tissue (BAT) and to use XECT to assess differences in BAT distribution and perfusion between lean, obese, and diabetic nonhuman primates (NHPs). Methods Whole‐body XECT imaging was performed in anesthetized rhesus and vervet monkeys during adrenergic stimulation of BAT thermogenesis. In XECT images, BAT was identified as fat tissue that, during xenon inhalation, underwent significant radiodensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Imaging experiments confirmed that this resonance originated primarily from 129 Xe spins located within the supraclavicular fat depot, where BAT is known to be present in humans. Overall, these results mimic the results previously obtained in rodents and non-human primates, which have shown a selective increase in xenon uptake in the brown fat of anesthetized mice and non-human primates during stimulation of thermogenesis by catecholamines 34 , 38 , 42 . In humans, the absence of a strong lipid peak before stimulation of thermogenesis confirms that at thermoneutrality BAT is not very well perfused, leading to reduced wash-in rate and low uptake of polarized 129 Xe atoms in the tissue.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Imaging experiments confirmed that this resonance originated primarily from 129 Xe spins located within the supraclavicular fat depot, where BAT is known to be present in humans. Overall, these results mimic the results previously obtained in rodents and non-human primates, which have shown a selective increase in xenon uptake in the brown fat of anesthetized mice and non-human primates during stimulation of thermogenesis by catecholamines 34 , 38 , 42 . In humans, the absence of a strong lipid peak before stimulation of thermogenesis confirms that at thermoneutrality BAT is not very well perfused, leading to reduced wash-in rate and low uptake of polarized 129 Xe atoms in the tissue.…”
Section: Discussionsupporting
confidence: 89%
“…While the solubility of xenon in fat is twenty fold higher than in any other tissue compartment 32 , 33 , low blood perfusion generally limits the concentration of xenon reached in fat after a single inhalation of the gas 34 . On the other hand, detectable concentrations of xenon are expected to be found in highly perfused fat tissues like brown fat, especially during stimulation of thermogenesis, when tissue blood flow increases 35 38 . Finally, the LDX chemical shift is very sensitive to the temperature-induced changes in the density of fat 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Oelkrug et al, 2015; Soppela et al, 1992) and non‐human primates (e.g. Garside et al, 2022; Williams et al, 2023).…”
Section: Resting Metabolic Rate Total Energy Expenditure (Tee) and Br...mentioning
confidence: 99%
“…This was demonstrated not only in lean mice, which present a very hydrated and perfused BAT, but also in obese mice in which the main interscapular BAT morphologically resembles beige fat. More recently, this technique was used to detect small clusters of BAT located within the supraclavicular, axillary, and perirenal regions of lean non-human primates and non-human primates with obesity 27 .…”
Section: Introductionmentioning
confidence: 99%